Proceedings of the ACM Symposium on Virtual Reality Software and Technology 1999
DOI: 10.1145/323663.323670
|View full text |Cite
|
Sign up to set email alerts
|

Coping with inconsistency due to network delays in collaborative virtual environments

Abstract: Collaborative Virtual Environments (CVEs) are shared virtual spaces designed to enhance collaboration between the -usually remote -participants. The deployment of Collaborative Virtual Environments over wide area networks increases typical network delays, potentially breaking the consistency between the replicated versions of an environment at the participants' sites. This paper presents our qualitative observations of an experiment involving two players engaged in a virtual ball game in the presence of increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 8 publications
2
77
0
Order By: Relevance
“…In a virtual ping-pong game that has large interaction granularity, users did not seem to perceive less than 150 ms latency, and were able to keep playing up to latencies of 500 ms [22]. In contrast, a study of a racing game, where players interact more quickly, showed that latency above 100ms made the game difficult [18].…”
Section: Network Delay and Its Effects On Collaborationmentioning
confidence: 94%
See 1 more Smart Citation
“…In a virtual ping-pong game that has large interaction granularity, users did not seem to perceive less than 150 ms latency, and were able to keep playing up to latencies of 500 ms [22]. In contrast, a study of a racing game, where players interact more quickly, showed that latency above 100ms made the game difficult [18].…”
Section: Network Delay and Its Effects On Collaborationmentioning
confidence: 94%
“…Delays can have severe effects on collaboration -on coordination, communication, and understanding of the shared situation [2,9,18,22]. Delay can make turn taking difficult to negotiate, can hinder social locking protocols, and can cause inconsistencies that lead to confusing rollback actions.…”
Section: Network Delay and Its Effects On Collaborationmentioning
confidence: 99%
“…Limited previous research has considered delay effects on collaborative task performance in 3D virtual environments (e.g. Park and Kenyon 1999, Vaghi et al 1999). One study suggests that performance is negatively affected by latencies of only 200ms (Park and Kenyon 1999), but the "two-person thread the needle" task used differs substantially from tasks in most 2D sharedworkspace groupware systems.…”
Section: Types Of Delay: Latency and Jittermentioning
confidence: 99%
“…One study suggests that performance is negatively affected by latencies of only 200ms (Park and Kenyon 1999), but the "two-person thread the needle" task used differs substantially from tasks in most 2D sharedworkspace groupware systems. A qualitative study (Vaghi et al 1999) saw a variety of strategy changes in the presence of latencies from 200ms -1000ms, and suggests that the task became difficult at about 500ms latency.…”
Section: Types Of Delay: Latency and Jittermentioning
confidence: 99%
See 1 more Smart Citation